Spaceborne GNSS reflectometry for ocean winds: First results from the UK TechDemoSat-1 mission - Foti, Giuseppe; Gommenginger, Christine; Jales, Philip; Unwin, Martin; Shaw, Andrew; Robertson, Colette; Roselló, Josep (Geophysical research letters, 2015)
First results are presented for ocean surface wind speed retrieval from reflected GPS signals measured by the low Earth orbiting UK TechDemoSat‐1 satellite (TDS‐1). Launched in July 2014, TDS‐1 provides the first new spaceborne Global Navigation Satellite System‐Reflectometry (GNSS‐R) data since the pioneering UK‐Disaster Monitoring Mission (UK‐DMC) experiment in 2003. Examples of onboard‐processed delay‐Doppler maps reveal excellent data quality for winds up to 27.9 m/s. Collocated Advanced Scatterometer (ASCAT) winds are used to develop and evaluate a wind speed algorithm based on signal‐to‐noise ratio (SNR) and the bistatic radar equation. For SNRs greater than 3 dB, wind speed is retrieved without bias and a precision around 2.2 m/s between 3 and 18 m/s even without calibration. Exploiting lower SNR signals, however, requires good knowledge of the antenna beam, platform attitude, and instrument gain setting. This study demonstrates the capabilities of low‐cost, low‐mass, and low‐power GNSS‐R receivers ahead of their launch on the NASA Cyclone GNSS (CYGNSS) constellation in 2016. Key Points New global spaceborne Global Navigation Satellite System‐Reflectometry data set New GNSS‐R wind speed inversion algorithm and validation against ASCAT wind data Unbiased winds with 2.2 m/s precision for high SNR signals without calibration